The Life and Legacy of C. René Padilla (Theological Kronos, 2021)
This article is a tribute to C. René Padilla Jijón who left a mark in author ́s life and in a many other people. It pretends to make visible theological, hermeneutic and evangelical Padilla ́s position expressed in some of his multiply participations in congress like Lausana, lectures, and so on. The most important information about Padilla ́s perspective presented in this article is about comprehensive mission that exposed strongly in each chance, and the relationship between gospel and social church’s responsibility.
Keywords: Theology; hermeneutics; gospel; comprehensive misión and social church’s responsibility.